Evolutionary Reshaping of Fungal Mating Pathway Scaffold Proteins - Pierre Côte (American Society for Microbiology, 2011)
ABSTRACT Scaffold proteins play central roles in the function of many signaling pathways. Among the best-studied examples are the Ste5 and Far1 proteins of the yeast Saccharomyces cerevisiae. These proteins contain three conserved modules, the RING and PH domains, characteristic of some ubiquitin-ligating enzymes, and a vWA domain implicated in protein-protein interactions. In yeast, Ste5p regulates the mating pathway kinases while Far1p coordinates the cellular polarity machinery. Within the fungal lineage, the Basidiomycetes and the Pezizomycetes contain a single Far1-like protein, while several Saccharomycotina species, belonging to the CTG (Candida) clade, contain both a classic Far1-like protein and a Ste5-like protein that lacks the vWA domain. We analyzed the function of C. albicans Ste5p (Cst5p), a member of this class of structurally distinct Ste5 proteins. CST5 is essential for mating and still coordinates the mitogen-activated protein (MAP) kinase (MAPK) cascade elements in the absence of the vWA domain; Cst5p interacts with the MEK kinase (MEKK) C. albicans Ste11p (CaSte11p) and the MAPK Cek1 as well as with the MEK Hst7 in a vWA domain-independent manner. Cst5p can homodimerize, similar to Ste5p, but can also heterodimerize with Far1p, potentially forming heteromeric signaling scaffolds. We found direct binding between the MEKK CaSte11p and the MEK Hst7p that depends on a mobile acidic loop absent from S. cerevisiae Ste11p but related to the Ste7-binding region within the vWA domain of Ste5p. Thus, the fungal lineage has restructured specific scaffolding modules to coordinate the proteins required to direct the gene expression, polarity, and cell cycle regulation essential for mating. IMPORTANCE The mitogen-activated protein (MAP) kinase cascade is an extensively used signaling module in eukaryotic cells, and the ability to regulate these modules is critical for ensuring proper responses to a wide variety of stimuli. One way that cells regulate this signaling module is through scaffold proteins that insulate related pathways against cross talk, improve signaling efficiency, and ensure that signals are connected to the correct response. The Ste5 scaffold of the S. cerevisiae mating response is a well-studied representative of this class of proteins. Using bioinformatics, structural modeling, and molecular genetic approaches, we have investigated the equivalent scaffold in the pathogenic yeast Candida albicans. We show that the C. albicans protein is structurally distinct from that of Saccharomyces cerevisiae but still provides similar functions. Increases in pathway complexity have been associated with changes in scaffold connectivity, and overall, the tethering capacity of the scaffolds has been more conserved than their structural organization.